CLUBUL „BIBLIOTECA MOV” – UN NOU FEL DE A SPRIJINI ŞI DE A ÎNCURAJA PREZENŢA PROFESIONALĂ - CORGHENCI, director adjunct, Departamentul Informaţional Biblioteconomic, ULIM, Ludmila (BIBLIOPOLIS, 2020)
The creation in February 2011 of the Club Purple Library infl uenced the activity and the position of the members and participants to the Club meetings and of their institutions. The impact is reviewed in context of the various aspects: the development of librarian’s creativity, the support of professional community, the development of the managerial culture etc. The topics discussed at meetings were various: institutional identity, forms of promoting library services, public services 2.0, visual thinking and logic, professional reading etc. The benefi ts of the participation at the club meeting are: professional development, lifelong learning, new knowledge, communication.